2016
DOI: 10.4186/ej.2016.20.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Mathematical Modeling of the Oxidative Coupling of Methane in a Membrane Reactor

Abstract: Abstract. The oxidative coupling of methane (OCM) in a dense BSCFO membrane reactor (MR) was theoretically studied using a two-dimensional reactor model. The simulation results indicated that increasing the operating temperature results in increased CH4 conversion and decreased C2 selectivity. An increase in the methane feed flow rate lowers the CH4 conversion but increases the C2 selectivity; however, the effect of the air flow rate on the OCM membrane reactor exhibits an opposite trend. The optimum configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Through mathematical modeling, computational simulation, and theoretical study, the transport of heat and mass in different systems can also be understood, providing a useful insight into the design of OCM/NOCM systems in membrane reactors. ,,,,,,, …”
Section: Discussionmentioning
confidence: 99%
“…Through mathematical modeling, computational simulation, and theoretical study, the transport of heat and mass in different systems can also be understood, providing a useful insight into the design of OCM/NOCM systems in membrane reactors. ,,,,,,, …”
Section: Discussionmentioning
confidence: 99%
“…Based on the evaluated scientific papers, seven different main subject streams have been identified: (1) modelling of the OCM process, embracing phenomenological and empirical mathematical descriptions of reactors and respective chemical kinetics [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], but also involving theoretical analyses of mechanistic models [23][24][25][26][27][28][29]; (2) economic evaluation of actual OCM commercial implementations, involving the analysis of capital and operational costs [30][31][32][33][34][35]; (3) assessment of environmental impacts, mainly involving the analysis of CO 2 emissions [31]; (4) development of new and/or improved catalysts for the production of ethylene from OCM reactions [27,; (5) development of alternative processes for CH 4 conversion into ethylene and/or other products, including, for instance, the non-oxidative coupling of methane [74][75][76]; (6) investigation of downstream purification strategies [77][78][79], concerning mainly the separation of products from the OCM reactor output stream; and finally, (7) the design, optimisation and development of OCM reactors for ethylene production, including the analysis of distinct reactor concepts (such as chemical looping…”
Section: What Are Ocm Scientific Publications and Patents About?mentioning
confidence: 99%
“…Good agreement between the experimental data and simulations was observed (for CH4/O2 feed molar ratio of 2, at 1.1 bar and inlet temperature of 750 °C) and the authors concluded that fast OCM reactions can cause concentration gradients due to oxygen de- Holst et al [115] proposed a two-dimensional, pseudo-homogeneous model to describe the OCM packed-bed membrane reactor (PBMR), which used a generic ceramic membrane and a catalyst bed of La2O3/CaO. The model comprised steady-state mass, energy, and momentum balances, as illustrated by Equations ( 11)- (13), where boundary conditions accounted for the flux through the membrane for the reactor tube and shell (not shown) and the ten elementary steps of the reaction network developed by Stansch et al [92] were used to represent the net reaction rates. In Equations ( 11)-( 13), Ci is the concentration of reactant i; uz is the superficial velocity in the z axis (Figure 18); Dr is the effective diffusion coefficient in the r axis; Ri,j is the reaction rate for component i in reaction j; T is the temperature; cp is the heat capacity; λr is the heat transfer coefficient in the radial direction; ΔHRj is the reaction enthalpy of reaction j; P is the pressure; ρg and εk are the gas density and bed porosity, respectively; Re is the Reynolds number; and dk is the catalyst pellet size.…”
Section: Modelling Approaches For Membrane Reactorsmentioning
confidence: 99%
“…on finding novel reactor configurations, as membrane reactors [5], and more suitable OCM catalysts, meaning a better compromise between its selectivity, activity and stability [7]. These efforts are based on the fact that modelling calculations have shown promising results [8], [9], demonstrating that a proper optimization of the reactor design and operating conditions can lead to OCM reactor yields well above this 30% target (minimum to make the process economic).…”
Section: Figure 1 Forecast For the Normalized Price (Respect To 2016) Of Oil And Natural Gas For The Coming Period [1]mentioning
confidence: 99%